Kemampuan Auditor Terhadap Kualitas Audit Inspektorat Provinsi Riau - apriliani, ika berty (Komunitas Manajemen Kompetitif, 2016)
Abstract: This study aims to determine the effect of competence and due professional care on the quality of the audit results Internal Auditor at Inspectorate Riau Province (APIP). This study uses multiple regression analysis. The population in the study were all auditors in Riau Provincial Inspectorate totaling 52 people. The population is all auditors in Riau Province Inspectorate which totaled 52 people. While the number of samples using a sampling technique saturated / census sampling technique in which all members of the population used as a sample. The results showed that the statistically variable competence and due professional care have a significant effect on audit quality. The implications of this study emphasize the importance of the ability of auditors in each audit assignment. Keywords: Audit Quality, Competence, Due Professional Care